Heart disease in beef cattle: visual heart score and sarcocystis - Jensen, Makenna (My University, 2026)
Congestive heart failure (CHF) in feedyard cattle has been diagnosed at lower elevations, indicating elevation is not a necessary factor for CHF. Hypoxia from a variety of causes leads to vasoconstriction and pulmonary hypertension which can culminate in CHF. Sustained differences in the cardiac pressure gradient may result in morphologic changes of the heart such as ventricular and atrial enlargement. Understanding previous literature and the association between gross and histologic cardiac changes are important to advancing industry knowledge on this disease process. A narrative literature review was completed with the objective of providing an overview of the prevalence of sarcocystis infections found in beef cattle globally and regionally. Two databases (PubMed and AGRICOLA) were reviewed. A total of 59 articles from 1957 to 2026 were identified describing prevalence or epidemiology of sarcocystis in beef cattle. The intent of this review was to identify literature gaps surrounding the topic of sarcocystis infection in cattle, particularly within North America. The review identified 11 articles from Africa, 26 from Asia, 13 from Europe, 1 from North America, 4 from Oceania, and 4 from South America. Respectively the prevalence of sarcocystis in beef from each continent was 59%, 75%, 76%, 62%, 80%, and 96%. The objective of the first study was to evaluate gross heart score in cattle at slaughter with cardiac fibrosis, necrosis, or cardiomyofibrillar abnormalities. A total of 121 cases were stratified by heart score (HS) using a scale of 1 to 5. A HS of 1 represented a normal heart and a HS of 5 represented of severe remodeling with misshapen ventricles. Cattle were evaluated for gross lesions of the heart, lung, and liver including failure of lungs to deflate, pulmonary edema, pneumonia, and liver abscesses or congestion. Samples collected for histology included cardiac (n=4), pulmonary (n=4), and hepatic (n=1). Histologic evaluation scored cardiac and hepatic fibrosis and necrosis, embedded myocardial protozoal cysts (EMPC) were quantified, and pulmonary lesions were categorized. A total of 40 cases had a normal HS (1 or 2), and 63 cases had an abnormal HS (3, 4, or 5). A total of 64 cases had normal lung deflation scores (normal deflation), and 39 cases had abnormal lung deflation scores (mild, moderate, or severe failure of the lungs to deflate). Of the 103 total cases, 67 cases had EMPC in at least one cardiac section. Cattle with abnormal lung deflation scores were more likely to also have an abnormal HS (0.76±0.07, p≤0.01) compared with cattle with normal lung deflation scores (0.52±0.06). Cattle with EMPC present in at least one cardiac section were more likely to also have abnormal HS (0.73±0.05, p≤0.1) compared with cattle without EMPC (0.39±0.08). The objective of the second study was to determine if an association existed between EMPC and HS or CHF in cattle feedyard mortalities. A total of 121 cattle feedyard mortalities that underwent necropsy in 2022 and 2023 were included in this study. A veterinarian scored the hearts post-hoc on a scale of 0 to 5. A HS 0 was a heart with infectious disease, a score of 1 represented normal, and HS 5 represented a severely enlarged and misshapen heart. Mortalities were necropsied in the field and the cardiopulmonary, gastrointestinal, musculoskeletal, urinary, and reproductive systems were evaluated. Samples from the papillary muscle of the heart were collected for histologic evaluation. Cardiac samples were digitized and the presence of EMPC were counted along with a measurement of each sample area. The EMPC over the sample area was calculated for an embedded cardiac protozoal cyst ratio (EMPCR). After case removals, 106 cattle were left in the study population with a total of 73 heifers and 33 steers. Heart scores were categorized into normal HS (NHS) (HS 1 or 2), abnormal HS (AHS) (HS 3, 4, or 5), and infected (HS 0). There was a total of 60 NHS, 34 AHS, and 12 infected cases. A total of 15 cases were defined as having CHF which was defined as an AHS with two or more effusions of the pleural, pericardial, or peritoneal space with a congested liver. After statistical analysis, no association was found between AHS and EMPCR or cattle with CHF and EMPCR. Congestive heart failure in feedyard cattle has an increasing impact on the industry. While no associations were established between AHS and histologic changes of the heart, lungs, or liver, a significant association was found between the presence of EMPC and AHS in cattle at slaughter. This same association was not found in feedyard cattle mortalities. While these protozoan parasites have been considered incidental in the past, their association with AHS in feedyard cattle, potential implication on heart health, and pathogenesis should continue to be investigated.
Keywords: Heart score; Bovine congestive heart failure; Sarcocyst; Embedded myocardial protozoal cyst